A tale of two countries: all‐cause mortality among people living with HIV and receiving combination antiretroviral therapy in the UK and Canada. Issue 9 (24th April 2017) - Patterson, S; Jose, S; Samji, H; Cescon, A; Ding, E; Zhu, J; Anderson, J; Burchell, AN; Cooper, C; Hill, T; Hull, M; Klein, MB; et al.
Abstract : Objectives: We sought to compare all‐cause mortality of people living with HIV and accessing care in Canada and the UK. Methods: Individuals from the Canadian Observational Cohort (CANOC) collaboration and UK Collaborative HIV Cohort (UK CHIC) study who were aged ≥ 18 years, had initiated antiretroviral therapy (ART) for the first time between 2000 and 2012 and who had acquired HIV through sexual transmission were included in the analysis. Cox regression was used to investigate the difference in mortality risk between the two cohort collaborations, accounting for loss to follow‐up as a competing risk. Results: A total of 19 960 participants were included in the analysis (CANOC, 4137; UK CHIC, 15 823). CANOC participants were more likely to be older [median age 39 years (interquartile range (IQR): 33, 46 years) vs . 36 years (IQR: 31, 43 years) for UK CHIC participants], to be male (86 vs . 73%, respectively), and to report men who have sex with men (MSM) sexual transmission risk (72 vs . 56%, respectively) (all P < 0.001). Overall, 762 deaths occurred during 98 798 person‐years (PY) of follow‐up, giving a crude mortality rate of 7.7 per 1000 PY [95% confidence interval (CI): 7.1, 8.3 per 1000 PY]. The crude mortality rates were 8.6 (95% CI: 7.4, 10.0) and 7.5 (95% CI: 6.9, 8.1) per 1000 PY among CANOC and UK CHIC study participants, respectively. No statistically significant difference in mortality risk was observed between the cohort collaborations in Cox regression accounting for loss to follow‐up as a competing risk (adjusted hazard ratio 0.86; 95% CI: 0.72–1.03). Conclusions: Despite differences in national HIV care provision and treatment guidelines, mortality risk did not differ between CANOC and UK CHIC study participants who acquired HIV through sexual transmission.